Penguatan Legalitas UMK di Desa Tlontoraja melalui Pendampingan Sertifikasi Halal - Mahardhani Annisa Adzim; Elys fauziyah; Adjie Manggala Syahriyanda; Saufil Musyafiroh; Kusnul Kotimah; Muhammad Wildan Rahmanul Hakim; Fitria Nayla Putri (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Tlontoraja Village, Pasean District, Pamekasan Regency is one of the villages where the majority of the people are entrepreneurs in making products based on marine raw materials, such as petis, crackers, and rengginang. This type of entrepreneurship is classified as a micro and small enterprise (MSE). The free halal certification program for MSE products created by the government is not yet known to business actors in this village. Therefore, existing MSEs do not have halal certificates. The aim of this service activity was to socialize the halal certification program and provide assistance in its management. The method applied in the service is conducting outreach and discussions about halal certification, and then identifying MSEs who are willing to be accompanied in processing halal certificates. The result of the service that has been carried out is the socialization of the free halal certification program for MSEs delivered by the Halal Product Process (PPH) companion from the Agribusiness Study Program. Students have assisted in processing halal certification requirements, uploading documents to the halal website, and the MSEs accompanied have received halal certificates.